Constitutional Court of Indonesia Decision Number 90 After the MKMK Decision and Its Implementation - Pujanegara, Bayu Sukma; Sadino, Sadino; Lutfi, Anas (LEGAL BRIEF, 2024)
This research employs a normative juridical approach with a focus on legislative analysis. It evaluates how formal defects and ethical violations by judges impact legitimacy and public perception. The main findings indicate that these two decisions cast doubt on constitutional compliance and legal validity, highlighting the need for stronger review mechanisms and oversight to uphold the integrity of the Constitutional Court (MK). The purpose of this study is to identify the impact of formal defects and ethical violations by judges in Constitutional Court Decision No. 90 and Constitutional Court Honorary Council (MKMK) Decision No. 2/MKMK/L/11/2023 on constitutional legal principles in Indonesia. The conclusion shows that legal validity, constitutional compliance, finality, and the binding nature of Constitutional Court decisions, along with the integrity and reputation of the Constitutional Court, play significant roles in Indonesia’s constitutional law. It was found that Constitutional Court Decision No. 90 and MKMK Decision No. 2 of 2023, related to formal defects and ethical violations, have a significant impact on the legitimacy and public perception of the constitutional justice system. Although the finality and binding nature of Constitutional Court decisions are fundamental to legal certainty, a review mechanism is needed in certain situations, especially when formal defects or ethical violations occur. Formal defects and ethical violations can erode public trust and pose serious challenges to the dignity of the constitutional judiciary.